2019
DOI: 10.1093/carcin/bgz095
|View full text |Cite
|
Sign up to set email alerts
|

TSC22D2 identified as a candidate susceptibility gene of multi-cancer pedigree using genome-wide linkage analysis and whole-exome sequencing

Abstract: Cancer is a complex disease, which may involve multiple tumor susceptibility genes that mediate the occurrence and development of tumor molecular events. This study aimed to identify new genetic loci using genome-wide linkage analysis and whole-exome sequencing in a rare, large multi-cancer pedigree recently found in China. We performed high-throughput single-nucleotide polymorphism (SNP) array and linkage analyses of 24 core members of this pedigree and found that the disease susceptibility locus in the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…The sequences containing the putative miR‐1237‐3p and human PNN mRNA binding sites were amplified and cloned into the pMIR‐REPORT vector, and the sequences are shown in Table . Relative luciferase activity was measured by the Dual‐Luciferase Reporter Assay System (Promega, Madison, WI, USA) using SpectraMax ® iD3 microplate reader (Shanghai, China) (Xiao et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The sequences containing the putative miR‐1237‐3p and human PNN mRNA binding sites were amplified and cloned into the pMIR‐REPORT vector, and the sequences are shown in Table . Relative luciferase activity was measured by the Dual‐Luciferase Reporter Assay System (Promega, Madison, WI, USA) using SpectraMax ® iD3 microplate reader (Shanghai, China) (Xiao et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Malignant cell proliferation is one of the hallmarks of tumor cells [82][83][84][85][86]. Research has shown that c-Myc can promote the transcription of positive cell cycle regulatory factors, such as E2F transcription factors, cyclin D1, and cyclin-dependent kinase 4 (CDK4).…”
Section: Pvt1 Participates In the Proliferation-related Signaling Patmentioning
confidence: 99%
“…BRAF gene mutations are associated with the development of a variety of tumors, such as melanoma [5], lung cancer [6], colorectal cancer [7] and thyroid cancer. In recent years, a large body of literature has shown that the BRAF V600E mutation is associated with a series of adverse clinical pathological factors in PTC, such as advanced disease, invasive characteristics, and others [8][9][10][11][12][13][14]. Many studies have shown that the BRAF V600E mutation may result in the activation of downstream genes of the MAPK pathway, which may lead to a slight downregulation of the sodium iodide symporter (NIS), thereby causing an inaccurate NIS localization wherein the NIS cannot be accurately localized to the cell membrane [15,16].…”
Section: Introductionmentioning
confidence: 99%